Political Marketing Factors Determining Advantages Intention to Vote (Study on Tubanregency Election December 2020) - Rahayu RAHAYU; Puji HANDAYATI (Indonesia Strategic Sustainability, 2022)
This study aims to examine the variables of political marketing to get the most votes. This variable is a technique and control of a system so that the campaign team is successful in general elections to win or get the most votes in the political arena. For this reason, the success team must understand strategies in political marketing, which include intimacy, personal connections, trust, intention to vote, personal connections, and word of mouth. The research approach method uses quantitative because this research focuses on hypothesis testing so that the research process can be carried out in a structured manner and uses a large sample. Research result Familiarity has a significant effect on personal connection in political marketing in the 2020 Tuban Regency election. Familiarity has no significant effect on Trust in political marketing in the 2020 Tuban Regency election. Familiarity has a significant effect on the intention to vote in political marketing in the 2020 Tuban Regency election. The personal connection has a significant effect on Trust in political marketing in the 2020 Tuban Regency election. Trust has a significant effect on word of mouth in political marketing in the Tuban Regency election in 2020. Trust significantly affects the intention to vote in political marketing in the 2020 Tuban Regency post-conflict local election. Intention to vote has a significant effect on word of mouth in political marketing in the 2020 Tuban Regency post-conflict local election.